Reconceptualizing Autism: An Alternative Paradigm for Social Work Practice. Issue 1 (2nd January 2018) - Haney, Jolynn L.
ABSTRACT: Autism is a complex, often misunderstood condition. More than a neurological disorder, autism can also be viewed as a different cognitive style or an alternative way of perceiving and reacting to the world. As more individuals on the autism spectrum are making themselves known, social workers must be open to using new paradigms to meet the needs of this unique population. This article explores how horizontal diversity and neurodiversity can be used to expand the ways social workers conceptualize autism and, consequently, how they work with persons on the autism spectrum and their families.